2016
DOI: 10.1016/j.sorms.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Classification methods applied to credit scoring: Systematic review and overall comparison

Abstract: The need for controlling and effectively managing credit risk has led financial institutions to excel in improving techniques designed for this purpose, resulting in the development of various quantitative models by financial institutions and consulting companies. Hence, the growing number of academic studies about credit scoring shows a variety of classification methods applied to discriminate good and bad borrowers. This paper, therefore, aims to present a systematic literature review relating theory and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
135
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 152 publications
(238 reference statements)
1
135
0
10
Order By: Relevance
“…Risk management and investment banking [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] classification (DT, NN, SVM, NB, LR), k-mean clustering UCI Repository International Dataset [41,42,45], Australia [51], Iran [37], Indonesia [34], China [35], German [36,38,39,51], Taiwan [51], US [49], Canada [46] Credit scoring, credit granting, risk management for peer-to-peer lending.…”
Section: References Key Techniques Regions Purposesmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk management and investment banking [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] classification (DT, NN, SVM, NB, LR), k-mean clustering UCI Repository International Dataset [41,42,45], Australia [51], Iran [37], Indonesia [34], China [35], German [36,38,39,51], Taiwan [51], US [49], Canada [46] Credit scoring, credit granting, risk management for peer-to-peer lending.…”
Section: References Key Techniques Regions Purposesmentioning
confidence: 99%
“…For instance, Lessmann et al [43] reported on relevant research up until 2014 and conducted comprehensive experiments with real life Australian and German credit data sets for seeking the optimal classifier. Louzada et al [44] recently produced a systematic review that specifically focused on the applications of classification techniques for credit scoring. Here, the main classification methods for credit scoring were summarized and introduced along with a detailed analysis of theoretical and paradigm trends.…”
Section: Risk Management and Investment Bankingmentioning
confidence: 99%
“…As a result of such use of SIS in insurance, valuable expert time can be allocated where it is most needed while keeping the risk assessment up-to-date and available for all of its users. Automatic credit risk scoring systems, based on ML algorithms, are behind most current credit decisions and aid in calculating insurance premiums to cover different types of credit based on the risk of defaulting payment (Louzada, Ara, & Fernandes, 2016).…”
Section: Predictive Risk Intelligence In Insurancementioning
confidence: 99%
“…General literature reviews of issues related to credit scoring modeling may be found in Thomas et al (2005), Abdou & Pointon (2011), Lessmann et al (2015), Louzada et al (2016) and Für et al (2017), for instance.…”
Section: Bibliographic Reviewmentioning
confidence: 99%